2006
DOI: 10.1083/jcb.200607025
|View full text |Cite
|
Sign up to set email alerts
|

p14–MP1-MEK1 signaling regulates endosomal traffic and cellular proliferation during tissue homeostasis

Abstract: The extracellular signal-regulated kinase (ERK) cascade regulates proliferation, differentiation, and survival in multicellular organisms. Scaffold proteins regulate intracellular signaling by providing critical spatial and temporal specificity. The scaffold protein MEK1 (mitogen-activated protein kinase and ERK kinase 1) partner (MP1) is localized to late endosomes by the adaptor protein p14. Using conditional gene disruption of p14 in mice, we now demonstrate that the p14–MP1-MEK1 signaling complex regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(236 citation statements)
references
References 24 publications
13
223
0
Order By: Relevance
“…The potential role of endosomal localization of MP1 in focal adhesion turnover is not yet known and will be discussed below. However, of particular interest is the recent finding that MP1, p14 and MEK control endosomal localization [131], perhaps consistent with a role for ERK regulation of endocytosis of adhesion components or trafficking of signaling proteins to and from dynamic adhesions (see below).…”
Section: Erk Regulation Of Rho-rock Functionmentioning
confidence: 71%
See 1 more Smart Citation
“…The potential role of endosomal localization of MP1 in focal adhesion turnover is not yet known and will be discussed below. However, of particular interest is the recent finding that MP1, p14 and MEK control endosomal localization [131], perhaps consistent with a role for ERK regulation of endocytosis of adhesion components or trafficking of signaling proteins to and from dynamic adhesions (see below).…”
Section: Erk Regulation Of Rho-rock Functionmentioning
confidence: 71%
“…EGF stimulated ERK does not colocalize with MP1/p14 on late endosomes at early time points suggesting sustained activation of ERK might require endosomal maturation or transfer of MEK and ERK from an early endosomal compartment to the late endosomal population containing MP1/p14. Alternatively, MP1 and/or p14 might directly regulate the localization of active ERK since recent evidence has shown that MP1/p14 is required for the correct localization of late endosome/lysosome compartment to the perinuclear regions in the cell [131] and might have a role in endosomal biogenesis [154].…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%
“…Thereby cells use a rather simple regulatory principle to control complex and highly specific biological responses during MAPK signaling. Not surprisingly, loss of this fine tuned control of temporal or spatial regulation of MAPK signaling by mutations or changes in expression of scaffold proteins regulating MAPK signaling can make a significant contribution to many different diseases, including infection, immunosupression, and cancer [Pawson, 2004; Teis et al, 2006; Bohn et al, 2007]. …”
Section: Receptor Signaling En Route To Lysosomesmentioning
confidence: 99%
“…However, ERKs extranuclear component is just as important. It has been estimated that half of the ERKs content remains in the cytoplasm after stimulation [62] and processes such as the formation of cell-matrix contacts, [63] adhesion, [64] endosomal traffic, [65] Golgi fragmentation, [66] and anti-apoptotic signaling [67] are dependent on ERK extranuclear activity. It fact, nearly half of the $180 proteins thus far identified as ERKs substrates, are non-nuclear proteins.…”
Section: Some Space For Erksmentioning
confidence: 99%
“…Some of them, like KSR1 and MP1, have no other known function but to regulate ERKs, and so, in principle, no pleiotropy-based undesired effects should be expected. Genetic ablation of p14, the scaffold protein through which MP-1 binds to endosomes, resulted in severe effect on the epidermis, [65] which, a priori, raises concerns about the safety of targeting the p14-MP1-ERK complex. It will be important to learn whether MP-1 deletion recapitulates this phenotype.…”
Section: Local Intervention For the Prevention Of Global Malignancy?mentioning
confidence: 99%